The Effect of Discounts and Free Shipping on Shopee Marketplace Purchase Decisions with Advertising as Intervening Variable - Nurainun Nurainun; Abd. Rasyid Syamsuri (Budapest International Research and Critics University, 2022)
This study intends to examine the impact of free shipping and discounts on consumer purchasing decisions on the Shopee marketplace with advertising as an intervening variable. The Triviona Residential Community in Dusun VI Marindal II, North Sumatra, Indonesia, serves as the study's sample. Probability sampling using a straightforward random procedure and a sample size of 213 participants was the sampling technique employed in this investigation. SEM (Structural Equation Model) is used in this data analysis technique. The study's findings demonstrate that offering free shipping has a positive and significant impact on advertising. While the discount has a negative and insignificant impact on advertising. Free shipping has a negative and insignificant effect on buying choices. Subsequent research has demonstrated that discounts have a positive and significant impact on purchase choices. Purchase decisions are positively and significantly impacted by advertising. Then, through advertising, free delivery has a positive and significant impact on purchasing decisions. Discounts have a negative and insignificant impact on consumer decisions made as a result of advertising.